Выражение и найти его значение при у=-2 (3у+2)^2 - (у+4)(2у-1)-5у 75

bogdanb13 bogdanb13    3   21.09.2019 04:10    0

Ответы
Кица234 Кица234  08.10.2020 06:14
(3у+2)^2 - (у+4)(2у-1)-5у = 9у² + 2*3у*2 + 4 - (2у² - у + 8у - 4) - 5у= 9у²+12у+4 - 2у²+у - 8у+4 - 5y= 7у² + 8

подставляем
7* (-2)² +8=7*4+8=36
ПОКАЗАТЬ ОТВЕТЫ
banana1106 banana1106  08.10.2020 06:14
... = (9у^2+12y+4) - (2y^2-y+8y-4) - 5y = 
= 9y^2+12y+4-2y^2+y-8y+4-5y =
= 7y^2+8 = 7*(-2)^2+8 = 7*4+8 = 28+8 = 36
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра